Balinese Shadow Puppet Characters Detection In The Wayang Peteng Performance Using The Yolov5 Algorithm - I Gusti Ngurah Bagus Putra Asmara; Made Windu Antara Kesiman; Gede Indrawan (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
To generate greater public interest in Balinese shadow puppet performances, it is crucial to explore novel ways of educating viewers about the characters showcased in the plays, as many individuals may need to become more familiar with them. In Object Detection, an algorithm is called You Only Look Once (YOLO). This research utilizes the YOLOv5 algorithm to detect Balinese shadow puppet characters in the